If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(y + 1) = -9 Reorder the terms: -9(1 + y) = -9 (1 * -9 + y * -9) = -9 (-9 + -9y) = -9 Add '9' to each side of the equation. -9 + 9 + -9y = -9 + 9 Combine like terms: -9 + 9 = 0 0 + -9y = -9 + 9 -9y = -9 + 9 Combine like terms: -9 + 9 = 0 -9y = 0 Solving -9y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-9'. y = 0 Simplifying y = 0
| 4(-6)-2y=-22 | | 14+(-15)= | | Y=Z-4x | | -.25(n+5)=2 | | F(1.5)=3x-2 | | 4a+3(2a+4)=24 | | -5p+7(3p+7)=-39-6p | | 8(2n-5)=-1/2(6n-2) | | .375b+18=-2.25 | | -19+-6= | | 0.7n+5.4=-1.6 | | 3-6h=-13/6 | | 3y+1=2y+7 | | 0.7+5.4=-1.6 | | 9x^2-6x=16 | | 4x^2+14x+3=0 | | -19+(-6)= | | 0.7+5.4=-13/5 | | x^3+3x^2-5x-39=0 | | -3(k+6)=-4k-25 | | 4x+60=40 | | 6-x=12x^2 | | 3(4v+1)-3(2v+3)=2(v-7)+w | | 34+4x=-6(1+6x) | | -x+6y=-22 | | x^2=-9x-4 | | x-2(-2)=14 | | n/99=-1 | | 4=3+x | | 4y-9y=10.5 | | 3y-7=-1 | | y=x^2+9x+4 |